2000
DOI: 10.1038/sj.leu.2401903
|View full text |Cite
|
Sign up to set email alerts
|

The interleukin-3 receptor alpha chain is a unique marker for human acute myelogenous leukemia stem cells

Abstract: Recent studies suggest that the population of malignant cells found in human acute myelogenous leukemia (AML) arises from a rare population of leukemic stem cells (LSCs). LSCs have been documented for nearly all AML subtypes and have been phenotypically described as CD34 + /CD38 − or CD34 + /HLA-DR − . Given the potentially critical role of these primitive cells in perpetuating leukemic disease, we sought to further investigate their molecular and cellular characteristics. Flow cytometric studies using primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
558
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 729 publications
(587 citation statements)
references
References 34 publications
25
558
0
4
Order By: Relevance
“…CD34pos CD38neg cells, which are enriched in AML-LSCs for patients with CD34-positive AML, from 16 of 18 primary AML samples showed strong expression of CD123. 40 Another prominent study also reported CD123 expressed on the surface of CD34pos CD38neg AML cells, but in this study the antigen was also present on the corresponding cellular subsets from healthy bone marrow (BM) and cord blood (CB), although expression levels on the enriched normal BM cells were at least 10-fold lower than on on the corresponding AML cells. 12 CD123 is also expressed on normal HSCs from AML patients in follow-up after induction therapy.…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…CD34pos CD38neg cells, which are enriched in AML-LSCs for patients with CD34-positive AML, from 16 of 18 primary AML samples showed strong expression of CD123. 40 Another prominent study also reported CD123 expressed on the surface of CD34pos CD38neg AML cells, but in this study the antigen was also present on the corresponding cellular subsets from healthy bone marrow (BM) and cord blood (CB), although expression levels on the enriched normal BM cells were at least 10-fold lower than on on the corresponding AML cells. 12 CD123 is also expressed on normal HSCs from AML patients in follow-up after induction therapy.…”
Section: Introductionmentioning
confidence: 57%
“…7,1012,40,46 We are not aware of any published reports indicating that they should differ from AML blasts in their intrinsic susceptibility to RDL by antibodies or antibody-derived agents in combination with NK cells. For most patients with CD34-positive AML, the relapse-relevant AML-LSCs are contained predominantly in the compartments of CD34-positive and (CD34-positive CD38-negative) cells.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations